Ferry Cruise Scheduler Information System Development Applying Spiral Method - Jimi Asmara; Tri Ana Setyarini; Gregorius Rinduh Iriane (STMIK Budi Darma, 2021)
Information technology is familiar to the public as it is today, the presence of various innovations in the field of information technology has facilitated all human activities both directly and indirectly. PT ASDP Kupang branch is a national company engaged in crossing services that serve the community in the east nusa tenggara region, as for the problems that exist so far the people of east Nusa Tenggara have difficulty in accessing information about the ship's cruise schedule, passenger fare information and other information related to the cruise prospective passengers are required to come directly to the office to find the required information. This information system is created to help people who use ferry crossing services in East Nusa Tenggara province, The result of this application is that users can check the ship departure schedule, fare info, cruise routes and information related to ferry cruises in East Nusa Tenggara in real time anytime and anywhere by using a computer or smartphone connected to the internet network this application is made using PHP and Mysql programming languages